Analiza ključnih dejavnikov vpliva na zadovoljstvo gostov v različnih kategorijah hotelov - Zabukovec Baruca, Petra (Naše gospodarstvo, 2011)
This paper examines the relationship between hotel service quality and guest satisfaction in different categories of hotels, focusing on key factors of service quality and their impact on guest satisfaction. To this end, empirical research was conducted, and the results indicated different guest satisfaction in the same category of hotels due to differences among key elements of the technical and functional quality. Thus, the conclusion was drawn that the expectations of guests visiting the hotel are usually focused on a recognizable quality standard based on the category of the hotel. The findings indicated that the main goal of the hotels is to ensure guest satisfaction by managing the gap between expectations and perception of received quality of service. Therefore, hotels should implement permanent measures of the quality of service systems to encourage hotel operators to improve their service quality, which may lead to changes in hotel performance and influence a higher level of guest satisfaction.
Keywords: hoteli; hotelirstvo; storitve; kvaliteta; gostje; zadovoljstvo